Tarybų Lietuvos knygos tarptautinėse ir užsienio parodose bei konkursuose 1940–1972 m. - Starkūnaitė, Vanda (Knygotyra, 1976)
The industry of Lithuanian polygraphy may be proud of its production from the middle of the sixth decade. A great part of such achievement belongs not only to the technical equipments but to the painters – book illustrators as well. Exhibitions of books are described according to two types: competitional exhibitions and represential (non-competitional) exhibitions. The latter is devided and discussed more in detail according to the type of organizing: books exhibited in cultural and art decade (Poland, Romania, GDR, Mongolia, India), books exhibited at international industry and commerce fairs, world “EKSPO” exhibition, or according to organizations: allied unification “Mezdunarodnaja kniga”, Society of cultural relations with foreign countries or the biggest libraries of republic sometimes organizing their exhibitions abroad. There were seperately discussed exhibitions-competitions because the works of Soviet Lithuanian polygraphers, book illustrators, designers were highly appreciated. At the International Book Exhibition in Moscow devoted to the 50th aniversary of the Great October Socialist Revolution Lithuania won 39 diplomas. International Book Exhibition devoted to the 100th year aniversary of Lenin’s birthday had awarded “Lithuanian Photography” with “Ivan Fiodorov” diploma. In Leipzig at the International Book Exhibition (1959, 1965, 1971) Lithuanian books were awarded with 2 gold, 2 silver, 3 bronze medals and one special diploma. A diploma was got at the International Text-book Fair in Leipzig 1968. At the International Exhibition of publications of Universities and Academies of Sciences in Bolonia (Italy, 1969) E. Laucevičius won gold medal for his atlas “Paper in Lithuanian in XV–XVIII centuries”. In 1967 and 1969 at the International Exhibition of Children Book Illustrations in Bratislava Lithuanian books “Frog Queen” by K. Kubilinskas and “Golden Sieve” by J. Rainis were awarded the first prizes and painters A. Steponavičius and B. Žilytė got prizes of “Gold Apple”. Wide geography of exhibitions and rich appraisals show the growth of book art in Soviet Lithuanian.